Biofortification of common buckwheat microgreens and seeds with different forms of selenium and iodine. (8th April 2019) - Germ, Mateja; Stibilj, Vekoslava; Šircelj, Helena; Jerše, Ana; Kroflič, Ana; Golob, Aleksandra; Maršić, Nina K
Abstract: BACKGROUND: The biofortification of crops can counteract human diseases, including selenium (Se) and iodine (I) deficiencies in the diet. Little is known about the effects of combinations of Se and I on microgreens and seeds, or on their accumulation in these tissues. The present study aimed to evaluate Se (SeO3 2−, SeO4 2− ) and I (I −, IO3 − ) biofortification of common buckwheat microgreens and seeds with respect to the effects of the addition of Se, I and Se + I on yield and on physiological and biochemical characteristics. RESULTS: In combination treatments, microgreens yield (600–800 g m −2 ) was 50–70% higher than for Se and I alone. The respiratory potential also increased by 60–120%. F v / F m was close to 0.8 in all samples. Se content [0.24 μg g −1 dry weight (DW)] was 50% higher for combination treatments than for Se and I alone. I content was highest for IO3 − treatment (216 μg g −1 DW) and decreased in combination treatments with Se by 50%. CONCLUSION: Biofortification of buckwheat microgreens with Se and I should be performed with care because there are synergistic and antagonistic effects of these elements with respect to their accumulation. IO3 − for the biofortification of microgreens should be kept low to prevent exceeding the recommended daily intake of I. © 2019 Society of Chemical Industry